Health economic evaluations of diagnostic tests for tuberculosis: a narrative review - Cemre Arpa; Ahmed Abd El Wahed; Serap Aydin; Prakash Ghosh; Dinesh Mondal; Lydia Nakiyingi; Julius Boniface Okuni; Sophie Schneitler; Manfred Weidmann; Martin Siegel (Health Economics Review)
Abstract Background Tuberculosis is the leading cause of death from infectious diseases globally. Non-specific symptoms and limitations of existing diagnostics involve challenges for informed policymaking and clinical practice. This paper reviews common practices in reporting the selection and definition of cost and effect parameters, and in reporting the translation of effect parameters into utility and disability weights, in health economic evaluations of TB diagnostic tests. Methods A targeted literature search in PubMed, Cochrane Library, Web of Science, and Google Scholar identified health economic evaluations of diagnosis and population screening strategies for TB. Results We found 28 studies comprising 11 cost-effectiveness and 17 cost-utility analyses. Observed patient data were used in 6 studies, 22 relied solely on model-based evaluations. Variations in prevalence, accuracy, and utility parameters were common, the Consolidated Health Economic Evaluation Reporting Standards terminology for costing was only used in 8 out of 28 studies. Discussion Future studies should state the exact type of TB studied, as it can manifest in multiple organs, remain inactive for long periods of time, and since different diagnostics can perform differently depending on the site involved it may influence test accuracies. Additionally, potential impacts of sequential diagnostics on test accuracy and the cost of inaction should receive more attention. Conclusion Precise terminology and transparent definitions of parameters and methodology in health economics evaluations are necessary to generate evidence that guides policymakers and supports clinical decision-making in the context of TB.